2020
DOI: 10.1007/s00521-020-05173-2
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal medical image fusion algorithm in the era of big data

Abstract: In image-based medical decision-making, different modalities of medical images of a given organ of a patient are captured. Each of these images will represent a modality that will render the examined organ differently, leading to different observations of a given phenomenon (such as stroke). The accurate analysis of each of these modalities promotes the detection of more appropriate medical decisions. Multimodal medical imaging is a research field that consists in the development of robust algorithms that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 52 publications
0
70
0
Order By: Relevance
“…Therefore, we can use deep learning for the detection of diseases from image data. Conversely, the image fusion algorithm was conducted for medical images where the big data was efficiently utilized (Tan et al 2020). Traditional deep learning techniques are used for detecting blood cells.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Therefore, we can use deep learning for the detection of diseases from image data. Conversely, the image fusion algorithm was conducted for medical images where the big data was efficiently utilized (Tan et al 2020). Traditional deep learning techniques are used for detecting blood cells.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Later on, NSSTs are widely explored because of the ability to offer anisotropic, multi-dimensional, multi-directional, and shift-invariant representation of the images with lower computational complexity [13,19,20]. Due to the several advantages, several researchers moved towards the NSST for image fusion giving improved fusion performances with the better preservation of structure detail information [15,16,[21][22][23].…”
Section: Related Workmentioning
confidence: 99%
“…13 and 14, it is observed that Liu et al [34] and the proposed methods can preserve more structural details but the colour information is better highlighted by the proposed method. Yin et al [31] and the [34], Yin et al [31], Li and Zhao [14], Tan et al [23], (left to right: second row) Panigrahy et al [32], Li et al [7], Proposed method…”
mentioning
confidence: 99%
See 2 more Smart Citations